Experimentation of The Flipped Classroom Learning Model And Inquiry Learning on Learning Achievement Reviewed From The Learning Styles of SMPN 1 Sukodono Students - Khotimah, Dinta Ameliana Khusnul; Nurcahyo, Adi; Swastika, Annisa (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to explore the impact of implementing inquiry learning and flipped classroom models on mathematics learning achievement, considering students' learning styles. The researcher employed a quantitative method through a 2x3 factorial experiment design. Data processing and analysis were conducted using a two-way ANOVA, followed by a post-ANOVA pairwise comparison using the Tukey HSD method. The population consisted of all students of SMP Negeri 1 Sukodono in the eighth grade of the academic year 2023/2024. A total of 27 students from class VIII D were assigned as experimental group I, and 27 students from class VIII F were assigned as experimental group II, each selected as samples for the study using cluster sampling or the random sampling method. Based on the results of the two-way ANOVA, it was found that there is a difference between the flipped classroom and inquiry learning models in improving students' learning achievement. The flipped classroom model was proven to be more effective than the inquiry learning model in enhancing students' mathematics learning achievement, with an average score of 75.356. There is an influence of learning styles on students' learning achievement; visual learning style was found to be better in improving students' learning achievement compared to auditory or kinesthetic learning styles. There is an interaction between the flipped classroom and inquiry learning models regarding learning achievement.